(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article examines the necessity of introduction of the latest computer technologies into the educational process to facilitate the formation of professional competence of the future specialists. To increase the effectiveness of educational services in teaching of accounting and analytical cycle disciplines for students the latest computer technologies should be introduced in the educational process to promote the formation of the professional competence of the future specialists. The key advantages of distance learning are its flexibility, the possibility of choosing study time, place and progress rate of learning individually. Nowadays the most attention is given to media environment the Moodle in creation of the distance learning courses. Considerable attention is paid to the choice of educational information. It should be modern, absolute, alternative. Such information should foster motivated data processing and require communication between the participants involved in order to enrich the information resources and improve the quality of results